INFORMATION CULTURE: POSITIVES AND NEGATIVES OF COMPUTER INFLUENCE (Pedagogy of Higher and Secondary Education, 2007)
The author reveals the tendencies of evolution of informational culture in modern society in the article, pensive and negative aspects of computer influence have been analyzed. The ways of informational and psychological protection of personality are being. presented.